Dust Exposure Associations with Lung Function among Ethiopian Steel Workers - Feyisa Girma; Zeyede Kebede (Ubiquity Press, 2019)
Background: Booming industrial development in Ethiopia, including a growing steel industry, may result in increased prevalence of pulmonary conditions. In this study, we evaluated steel workers' exposure to dust as well as its potential impact on lung function. Methods: Cross-sectional study of 75 steel workers in Ethiopia, interviewed from April to June 2015. We obtained information on respiratory symptoms and personal protective equipment use via interview and conducted spirometry testing to assess lung function. Dust samples were collected from different factory sections. Correlation analyses were used to assess associations between variables. Results: Maximum dust levels were recorded in the induction furnace, where both galvanized and non-galvanized metals are melted. Steel factory workers with higher levels of particulate matter exposure had increased rate of respiratory symptoms (r = 0.96). Forced vital capacity values showed a strong negative correlation with numbers of years at work (r = -0.86, p = 0.03) and responders age (-0.85, p = 0.49) and weak negative correlation with level of particular matter (PM) (r = -0.02, p = 0.07). Similarly, forced expiratory volume in 1 second was strongly negatively correlated with the number of years of exposure (r = -0.82, p = 0.05) and workers age (r = -0.85, p = 0.08) and weakly negatively correlated with PM level (r = 0.25, p = 0.67). Conclusions: Occupational exposure continues to be a major problem among steel factory workers in Ethiopia and is associated with lung function abnormalities. Ensuring the availability of proper personal protective equipment, regular factory inspections, and training may help mitigate the impact of occupational exposures among these workers.